THE IMPORTANCE OF DEVELOPING STUDENT YOUTH TRENDS THAT AFFECT MUSICAL PERCEPTION IN THE CONTEXT OF INNOVATIVE EDUCATION (American Journal of Research in Humanities and Social Sciences, 2023)
This article examines the essence of the development of trends that affect the musical perception of student youth by improving the professional skills of future music teachers in the context of innovative education.